Influence of coarse aggregate type on the damage mechanism in high‐strength concrete under compressive fatigue loading. (9th August 2019) - Scheiden, Tim; Oneschkow, Nadja
Abstract: This paper is published on the occasion of the 65th birthday of Prof. Dr.‐Ing. Ludger Lohaus, Director of the Institute of Building Materials Science, Leibniz University Hannover and coordinator of the SPP 2020, offering congratulations. Within the Priority Program SPP 2020 "Cyclic deterioration of High‐Performance Concrete in an experimental virtual lab, " the damage mechanisms of high‐performance concrete due to fatigue loading are investigated. At the Institute of Building Materials Science, Leibniz University Hannover, the influence of different concrete microstructures on the damage mechanisms is investigated in a conjoint project. Based on a systematic variation of concrete composition, for example, coarse grain aggregate, water/cement ratio and additives, different concrete mixtures, mainly high‐strength concrete, with different microstructures are created and systematically analyzed. The results of the fatigue tests are analyzed regarding different damage indicators, for example, strain development, stiffness development, and acoustic emission. The overall objective is to obtain comprehensive knowledge concerning the damage mechanisms by conjoint analyses of damage indicators and results of the imaging techniques and to provide specifically aligned data to calibrate numerical models within the conjoint project. For future investigations, high‐resolution imaging techniques, such as computer tomography and scanning electron microscope, will be applied to investigate the crack growth in the microstructure caused by fatigue loading. In this paper, the results of the analysis of the damage indicators for two high‐strength concretes differing only in the type of coarse aggregate used are presented comparatively.